Effects of orthodontic forces on pulp tissue - Pinandi Sri Pudyani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2006)
Numerous researches on pulp tissue changes caused by orthodontic forces have been performed, among others are: pulp angiogenesis, pulp tissue respiration rate, alkaline phosphatase and aspartate aminotransferase enzyme activities; micro vascular response inside the pulp and the effect of dental movement i.e. extrusion, intrusion, and torque. The result is still controversial, as some researchers claim that orthodontic force has a negative effect, others deny by saying there is no such effect on pulp tissue.